Brown dwarfs in Eddington-inspired Born-Infeld and beyond Horndeski theories - Rosyadi, A.S.; Sulaksono, A.; Kassim, Hasan Abu; Yusof, Norhasliza (SpringerOpen, 2019)
We studied herein the mass and the radius of brown dwarfs predicted by beyond Horndeski (BH) and Eddington-inspired Born-Infeld (EiBI) gravity theories by numerically solving the modified non-relativistic hydrostatic equations of both theories. We used a recent compilation of brown dwarf masses and radii obtained from Ref. Bayliss et al. (Astrophys J 153:1, 2016) to constrain the free parameter of both theories. We obtain the range of the corresponding parameters with 1σ and 5σ confidence by using chi-squared analysis. Furthermore, the minimum chi-squared values can be reached for the cases of κ=0.17×102m5kg-1s-2 and γ= - 0.1207 for EiBI and BH theories, respectively. The corresponding parameter values with the minimum chi-squared values are relatively small; therefore, they cannot significantly change the brown dwarf mass limits determined from the equivalence of nuclear and photosphere luminosities for the pp (hydrogen burning) and pp+pd (deuterium burning) reactions. © 2019, The Author(s).